2012
DOI: 10.2136/sssaj2011.0420
|View full text |Cite
|
Sign up to set email alerts
|

Corn Residue Removal Impact on Topsoil Organic Carbon in a Corn-Soybean Rotation

Abstract: Corn {Zea mays L.) residue is being considered as a feedstock for biofuels production. The impact of removing corn residue on soil productivity is not well understood. A corn-soybean [Glycine max (L.) Merr.] rotation was established in 2000 to determine the effect of removing corn residue at three rates (37, 55, and 98%) on soil organic carbon (SOC) in the 0-to 5-cm layer of soil after 8 yr. The effect of cover crops {slender wheatgrass [Agropyron caninum (L.) Beauv.] In corn and lentil {Lens culinaris Medik. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 41 publications
8
51
0
1
Order By: Relevance
“…as reported by Powlson et al [32]. In an 8-year field experiment, Stetson et al [4] found that as the rate of residue removal increased, soil organic matter, wet aggregate stability, the C/N ratio and microbial activity decreased significantly.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…as reported by Powlson et al [32]. In an 8-year field experiment, Stetson et al [4] found that as the rate of residue removal increased, soil organic matter, wet aggregate stability, the C/N ratio and microbial activity decreased significantly.…”
Section: Discussionsupporting
confidence: 52%
“…However, one aspect that is not often properly considered in the production of biofuels is the depletion of soil organic carbon (SOC) levels that may occur by removing crop residues (and hence carbon input) from cultivated fields [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with other rotations that included CC (Stetson et al, 2012;Wright and Anderson, 2000) and particularly the ones with grasses (Balota et al, 2014a;Rillig et al, 2002). The glomalin contents showed early increments, therefore, they might be considered also as a sensitive biological parameter.…”
Section: Resultssupporting
confidence: 91%
“…# Total gas flux from May to October + 12% for CO 2 , 15% for N 2 O, and 30% for CH 4 of the total flux from November to April (Liebig et al, 2010) (Tables 4 and 5). It has been known that crop residue removal can reduce soil C storage and C sequestration rates compared with not removing residue (Stetson et al, 2012). Greater C was lost from W-P/B-F than the other cropping sequences, probably due to a smaller amount of belowground crop residues returned to the soil as a result of the absence of crops during fallow.…”
Section: Global Warming Potential and Greenhouse Gas Intensitymentioning
confidence: 99%